A Passion for Policy ANZSOG Public Lectures 2005-2006 Series Essays in Public Sector Reform - Wanna, John (ANU Press, 2007)
This collection of papers is concerned with issues of policy development, practice, implementation and performance. It represents a range of views about diverse subjects by individuals who are, for the most part, in the public eye and who have the capacity to influence the shape and the reality of public policy. Each has a story to tell, with insights that can only be drawn by those working at the 'sharp end' of policy.